Dennis A. Rondinelli. Secondary cities in developing countries : policies for diffusing urbanization. [Beverly Hills] : Sage Publications, 1983, 288 p. (Sage library of social research ; 145) - Graizbord, Boris (Estudios Demográficos y Urbanos, 1986)
DENNIS A. RONDINELLI. Secondary Cities in Developing Countries. Policies for Diffusing Urbanization. Sage Library of Social Research 145, Sage Publications, 1983.